MENELAAH JOB SATISFACTION PADA PENDIDIK PAUD - Moh. Fikri Tanzil Mutaqin (Jurnal Anak Bangsa, 2022)
The work context will be much oriented that salary is a big support for jod satisfaction, however, that opinion is not fully justified. That money is not a complete support one gets satisfaction. These assumptions will then be discussed based on a job satisfaction theoretical framework which views work as a calling as a meaning for the usefulness of services for many people, so it is not a point of view of status, income, and prestige that is intended. This article presents the arguments against the Job Satisfaction of PAUD educators in the midst of material welfare problems that have not been fulfilled optimally. The core argument in this article is that the service process carried out fully and selflessly by PAUD teachers is kindness. Kindness in the psychological side that is done by a person allows to build valuable meaning and encourage satisfaction